Germany's reluctance to regulate related party transactions: An industrial organization perspective - Tobias Tröger (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
Germany Inc. was an idiosyncratic form of industrial organization that put financial institutions at the center. This paper argues that the consumption of private benefits in related party transactions by these key agents can be understood as a compensation for their coordinating and monitoring function in Germany Inc. As a consequence, legal tools apt to curb tunneling remained weak in Germany from the perspective of outside shareholders. While banks were in a position to use their firm-level knowledge and influence to limit rent-seeking by other related parties, their own behavior was not subject to meaningful controls. With the dismantling of Germany Inc. banks seized their monitoring function and left an unprecedented void with regard to related party transactions. Hence, a "traditionalist" stance which opposes law reform for related party transactions in Germany negatively affects capital market development, growth opportunities and ultimately social welfare.
urn:nbn:de:hebis:30:3-457757
Keywords: D23; D62; K22; 330; related party transactions; Germany Inc.; industrial organization; tunneling; private benefits of control; capital maintenance; group law